Spreadsheet For Heat Balance Calculation of Steam Power Plant (Case Study : Gresik Steam Power Plant) - Kurniawan Purba, Ridho
Steam power plant performance evaluation is significant. One of steam power plant performance parameter is heat rate. Heat rate describe how much input energy needed to produce electrical energy from generator. Heat rate of steam power plant usually written in heat balance document of plant. Heat balance calculation of steam power plant is complex because of involving lot of component. Nowadays, many software have been created for heat balance simulation of steam power plant. In this final project, spreadsheet for heat balance calculation of steam power plant is created. Spreadsheet is made using case study of Gresik steam power plant. Spreadsheet is made using thermodinamics principal searching for mass flow rate and balance pressure of feedwater heater. Spreadsheet is validated using software Cycle Tempo 5.0 on design load economical continious rating 100%, 75%, and 50%. Heat balance simulation using spreadsheet is done on operation condition outside design condition. This final project output is spreadsheet for heat balance calculation of Gresik steam power plant. Validation process show that spreadsheet largest deviation is about 0,48% for mass flow and 0,33% for balance pressure of feedwater heater.